KESESUAIAN PERTIMBANGAN HAKIM MAHKAMAH AGUNG MENOLAK KASASI PENUNTUT UMUM PADA PERKARA NARKOTIKA BERDASARKAN KUHAP - Khansa Diva; Bambang Santoso (Verstek, 2023)
This article analyzes the considerations of the Supreme Court judges in deciding the cassation request by the Public Prosecutor in Decision Number 2729 K/Pid.Sus/2022. The purpose of this article is to analyze the suitability of the Supreme Court Judge's considerations in deciding the cassation request by the Public Prosecutor in Decision Number 2729 K/Pid.Sus/2022 with the Criminal Procedure Code. The research method used is normative research, with the technique of collecting legal materials using library research where the types of legal materials used are primary legal materials and secondary legal materials. From the results of the study it can be concluded that the considerations of the Supreme Court Judge in deciding the Public Prosecutor's cassation request against narcotics cases in Decision Number 2729 K/Pid.Sus/2022 are in accordance with the Criminal Procedure Code, especially Article 254 and Article 255 paragraph (1) .Keywords: Cassation; Supreme Court; Narcotics; Consideration